2017
DOI: 10.1364/ol.42.003494
|View full text |Cite
|
Sign up to set email alerts
|

Secure communication systems based on chaos in optically pumped spin-VCSELs

Abstract: We report on a master and slave configuration consisting of two optically pumped spin-vertical-cavity surface-emitting lasers for chaos synchronization and secure communication. Under appropriate conditions, high-quality chaos synchronization is achieved. We propose two encryption schemes, where either the pump magnitude or polarization is modulated. The results show that these allow for Gb/s transmission of secure data, but exhibit different features: one indicates that the message can be recovered by the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…At the receiver end, the compound signal is firstly decrypted by the OTD module, and then the WDM modulated chaotic carriers (chaos + message) are derived from the decrypted signal and used for final message decryption. To numerically explore the dynamics of the ECSLs, the well-known Lang-Kobayashi rate equations are adopted, whose complex electric field amplitude E(t) and the intra-cavity carrier number N(t) of the MSL are written as [3][4][5][19][20][21] () 11 (1 )…”
Section: Theory and Numerically Modelling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At the receiver end, the compound signal is firstly decrypted by the OTD module, and then the WDM modulated chaotic carriers (chaos + message) are derived from the decrypted signal and used for final message decryption. To numerically explore the dynamics of the ECSLs, the well-known Lang-Kobayashi rate equations are adopted, whose complex electric field amplitude E(t) and the intra-cavity carrier number N(t) of the MSL are written as [3][4][5][19][20][21] () 11 (1 )…”
Section: Theory and Numerically Modelling Modelmentioning
confidence: 99%
“…Chaos communication has attracted extensive attention for its advantage of physical-layer security enhancement, since Pecora and Carrols demonstrated chaos synchronizations in two chaotic systems [1][2][3]. Over the last decade, external cavity semiconductor laser (ECSL) has been considered as one of the most promising candidates for all-optical chaotic communications, random bit generation and secure key distribution, since it is easy to obtain wideband chaotic signals from ECSLs with proper feedbacks [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Moskalenko et al 11 proposed a new method based on generalized synchronization for safety information transmission with significant stability to noise. In 2017, Li, N et al 19 reported a master-slave configuration that enables high-quality chaotic synchronization and secure communication, including two optically pumped rotating vertical cavity surface emitting lasers. In 2012, based on the stability theory of fractional-order systems, Wu X et al 13 proposed a new generalized projection synchronization of fractionalorder hyperchaotic systems and studied its application in secure communication.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, because of the limited bandwidth of the actual fading channel and/or signal detection necessities, filtering chaotic signals has an impact on the synchronization and error performance of the CBSC scheme, Jiang et al18 has studied this. In 2017, Li, N et al 19 reported a master-slave configuration that enables high-quality chaotic synchronization and secure communication, including two optically pumped rotating vertical cavity surface emitting lasers. In 2018, based on the cryptanalysis of the hyperchaotic image encryption scheme developed by Norouzi et al, Hossam et al 20 proposed a general image attack scheme of choice and revealed the key stream generated by it.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband chaotic semiconductor lasers have been extensively studied during the past several decades for their valuable applications in secure communications [1][2][3][4][5], random number generations [6][7][8][9][10][11][12], chaotic lidar [13,14], compressive sensing [15], and time domain reflectometry [16,17]. It is well-known that semiconductor lasers exhibit a rich variety of lasing dynamics with external perturbations such as optical feedback, laser injection, current modulation, and optoelectronic feedback [18][19][20].…”
Section: Introductionmentioning
confidence: 99%